KAJIAN FAKTOR PENENTU PRODUKTIVITAS TENAGA KERJA PANEN KELAPA SAWIT - Tennisya Febriyanti Suardi; Zahraturrahmi (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2026)
Palm oil harvester labor productivity is one of the important factors supporting the operational success of palm oil plantation companies, as it is directly related to both the quantity and quality of harvest yields. The level of labor productivity is influenced by various internal and external factors that determine the effectiveness and efficiency of harvesters’ performance in the field. This study aimed to examine and analyze the determinant factors affecting the productivity of palm oil harvest laborers at Torgamba Estate, North Sumatra. The research employed a quantitative approach, with the study location determined purposively and respondents selected through simple random sampling, involving 113 palm oil harvest workers. The data were analyzed using path analysis with the assistance of SPSS 23 software. The results showed that both internal and external factors had a positive and significant effect on the productivity of palm oil harvest laborers. Internal factors had an effect coefficient of 0.602, while external factors showed a more dominant effect coefficient of 0.794. The coefficient of determination value of 89.5% indicates that labor productivity was largely influenced by these two factors. The average productivity of palm oil harvest workers at Torgamba Estate reached 2,044 kg/Hk, with the majority classified within the moderate productivity category. The findings conclude that improving the productivity of palm oil harvest laborers requires integrated human resource management and an effective company work system. Therefore, companies are recommended to enhance job training, motivation, work discipline, employee welfare, and the provision of adequate work facilities to sustainably support labor productivity.